Reorganization of Basolateral Amygdala-Subiculum Circuitry in Mouse Epilepsy Model - Dongliang eMa; Jian Qiang eQu; Eyleen L Goh; Feng-Ru eTang (Frontiers Media S.A., 2016)
In this study, we investigated the reorganized basolateral amygdala (BLA)-subiculum pathway in a status epilepticus (SE) mouse model with epileptic episodes induced by pilocarpine. We have previously observed a dramatic loss of neurons in the CA1-3 fields of the hippocampus in epileptic mice. Herein, we observed a 43-57 % reduction in the number of neurons in the BLA of epileptic mice. However, injection of an anterograde tracer, Phaseolus vulgaris leucoagglutinin (PHA-L) into the BLA indicated 25.63 % increase in the number of PHA-L-immunopositive terminal-like structures in the ventral subiculum (v-Sub) of epileptic mice as compared to control mice. These data suggest that the projections from the basal nucleus at BLA to the vSub in epileptic mice are resistant to epilepsy-induced damage. Consequently, these epileptic mice exhibit partially impairment but not total loss of context-dependent fear memory. Epileptic mice also show increased c-Fos expression in the BLA and vSub when subjected to contextual memory test, suggesting the participation of these 2 brain areas in foot shock-dependent fear conditioning. These results indicate the presence of functional neural connections between the BLA-vSub regions that participate in learning and memory in epileptic mice.